Experimental characterization of the constitutive materials of MgB2 multi-filamentary wires for the development of 3D numerical models. (7th February 2017) - Escamez, Guillaume; Sirois, Frédéric; Tousignant, Maxime; Badel, Arnaud; Granger, Capucine; Tixador, Pascal; Bruzek, Christian-Éric
Abstract: Today MgB2 superconducting wires can be manufactured in long lengths at low cost, which makes this material a good candidate for large scale applications. However, because of its relatively low critical temperature (less than 40 K), it is necessary to operate MgB2 devices in a liquid or gaseous helium environment. In this context, losses in the cryogenic environment must be rigorously minimized, otherwise the use of a superconductor is not worthy. An accurate estimation of the losses at the design stage is therefore mandatory in order to allow determining the device architecture that minimizes the losses. In this paper, we present a complete a 3D finite element model of a 36-filament MgB2 wire based on the architecture of the Italian manufacturer Colombus. In order for the model to be as accurate as possible, we made a substantial effort to characterize all constitutive materials of the wire, namely the E – J characteristics of the MgB2 filaments and the electric and magnetic properties ( B − H curves) of nickel and monel, which are the two major non-superconducting components of the wire. All properties were characterized as a function of temperature and magnetic field. Limitations of the characterization and of the model are discussed, in particular the difficulty to extract the maximum relative permeability of nickel and monel from the experimental data, as well as the lack of a thin conductive layer model in the 3D finite element method, which prevents us from taking into account the resistive barriers around the MgB2 filaments in the matrix. Two examples of numerical simulations are provided to illustrate the capabilities of the model in its current state.